Microtubule assembly and in vitro development of bovine oocytes with increased intracellular glutathione level prior to vitrification and in vitro fertilization. Issue 4 (November 2014) - Hara, H.; Yamane, I.; Noto, I.; Kagawa, N.; Kuwayama, M.; Hirabayashi, M.; Hochi, S.
Summary Although vitrification is a useful technique for preservation of bovine oocytes, the yield of blastocysts derived from the vitrified oocytes is still low. We have recently reported a new type of cryoinjury, multiple aster formation, by which pronuclear migration and development of vitrified–warmed and in vitro-fertilized bovine oocytes are impaired. The aim of the present study was to investigate the effect of glutathione (GSH) content of vitrified bovine oocytes on multiple aster formation and subsequent in vitro development. Treatment of bovine cumulus–oocyte complexes with β-mercaptoethanol (βME) and l-cysteine (Cys) during in vitro maturation resulted in 2.5-fold higher GSH content not only in fresh control but also in vitrified–warmed oocytes. The percentage of normally fertilized zygotes exhibiting sperm aster(s) was >95% in all four groups (with or without βME/Cys × fresh control or vitrified). The frequency of multiple aster formation in vitrified oocytes (three-fold higher than that in fresh control oocytes) was not affected by the increased level of intracellular GSH with βME/Cys. Consequently, the migration and development of pronuclei as well as the yield of blastocysts from vitrified–warmed oocytes (17 versus 41%) were not improved. In addition, there was no effect of increased GSH level on the yield of blastocysts in fresh control groups.